PENGARUH VALUE CONGRUENCE DAN CORE SELF-EVALUATIONS TERHADAP JOB ENGAGEMENT DAN DAMPAKNYA PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Ignatius Soni Kurniawan (Universitas Sebelas Maret, 2018)
SMEs in Kasongan Bantul have a good reputation as SMEs that are able to penetrate in foreign markets. How OCB and Employee JE formed so that it can pull SMEs performance is the main issue being discussed in this research. Asking for 107 employees of SMEs in Kasongan craft industry bantul to fill in the questionnaire, this research can prove that value congruence directly or indirectly affects employee JE on OCB. Unfortunately, this research is unable to prove the effect of CSE on OCB direcly or indirecly.Keywords: value congruence, core self-evaluations, job engagement, organizational citizenship behavior.